PENGARUH PERILAKU GURU DAN MOTIVASI BELAJAR SISWA TERHADAP NILAI MATA PELAJARAN EKONOMI SISWA KELAS XI IPS SMA MURNI DI PADANG TAHUN AJARAN 2018/2019 - Debby Irawan (Jurnal Ecogen, 2018)
Abstract: This study aims to determine the Effect of Teacher Behavior on Learning Motivation, Effects of Learning Motivation on the Values of Economic Subjects of Social Sciences Class XI in Padang Pure High School and the Effect of Economic Subject Values in Class XI IPS in Padang Pure High School on Teacher Behavior. The population in this study were the eleventh grade students of SMA Murni Padang Academic Year 2018/2019 totaling 19 students. Data collection with questionnaires or questionnaires. The trial of the research instrument with validity test and reliability test was carried out on 19 students in Pure Padang High School. The data analysis technique used was using the SPSS program ver. 22.0. The results of this study are: First, there is a positive and significant influence of Teacher Behavior on Learning Motivation of Social Sciences Class XI Students in Padang Pure High School Academic Year 2018/2019, meaning that the better the Teacher's Behavior in learning process will increase students' motivation. Secondly there is a positive and significant influence of Teacher Behavior on Economic Subject Values of Social Sciences Class XI Students at Murni Padang High School Academic Year 2018/2019, it can be interpreted that the better the Teacher's Behavior in the learning process will increase Economic Subject Value of Class XI IPS in Pure High School Padang. Third, there is a positive and significant influence of Student Learning Motivation on the Eye Value of Economic Pelajran Students in Social Sciences Class XI in Padang Pure High School Academic Year 2018/2019 which shows that the higher students' learning motivation will also increase the results of economic class XI IPS in Pure High School Padang Academic Year 2018/2019.Keywords: Teacher Behavior, Learning Motivation and Economic Subject Value